Computer-assisted error analysis: A study of prepositional errors in the Brazilian subcomponent of the international corpus of learner english (Br-ICLE) - Recski, Leonardo Juliano (2002)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão.